Human papillomavirus vaccine uptake among 9–17 year old males in the United States: The National Health Interview Survey, 2010 - Laz, Tabassum H. (Landes Bioscience, 2013)
In 2009, a quadrivalent HPV vaccine was approved and “permissively” recommended for US males aged 9 to 26 y to protect against genital warts. The purpose of this study was to examine parental awareness and HPV vaccine uptake among 9–17 y old males during the first year following this recommendation. Data from the 2010 National Health Interview Survey (NHIS) were obtained to assess vaccination status (n = 2973) of this age group. Univariate logistic regression analysis was performed to examine correlates of parental awareness and uptake of the HPV vaccine. Overall, 55% of parents with sons were aware of the HPV vaccine. The likelihood of parental awareness was lower among minorities and adolescents with low family incomes, and higher among adolescents with insurance, higher parental education, and those who had a well-child check up and dental examination in the past year than their counterparts. Only 2.0% and 0.5% of 9–17 y old males initiated (≥ 1 dose) and completed (≥ 3 doses) the vaccine series, respectively. Adolescents with a Hispanic origin (odds ratio (OR) 2.03, 95% confidence interval (CI) 1.09–3.78), low family income (OR 2.89, 95% CI 1.48 -5.57), and history of influenza vaccination in the past year (OR 1.89, 95% CI 1.11 -3.22) were more likely than their counterparts to initiate the HPV vaccine. On the other hand, adolescents with private insurance (OR 0.44, 95% CI 0.20 -0.94) and those who had college educated parents (OR 0.45, 95% CI 0.22 -0.89) were less likely to initiate the vaccine. This study showed that very few adolescent males received any doses of HPV vaccine during the first year following its recommendation for this gender. Thus, interventional programs are needed to improve vaccine uptake among adolescent males.